Atribuição de causalidade e coping religioso/espiritual adotados pela Igreja Evangélica Nasci pra Deus frente à pandemia da covid-19 - Siqueira, Silvana Paula da Silva (2021)
The present work proposes a reflection on the role of the Evangelical Church “Nasci pra Deus” in the process of facing the Covid-19 pandemic, in the city of Guarulhos, São Paulo, from the theory of causal attribution and the concept of religious/spiritual coping. Our main goal was to understand, based on the attribution of causality adopted by this group, how the process of coping with the disease took place. Within the scope of a qualitative research, through individual interviews applied to 5 members of the context, answers were sought to the following questions: how the religiosity of these subjects has influenced the way they have been facing Covid-19 and how religiosity would be a facilitator agent in the process of facing the pandemic, as a social event? We used as theoretical reference the ideas of Kenneth Pargament on religious coping, and of Harold Heider on attribution of causality, and we made use of complementary references by the approaches of Religious Studies and Psychology of Religion. According to the data obtained, the strategies for coping with covid-19 adopted by the subjects of analysis had a strong influence on the preventive measures adopted. It was also concluded that the religious/spiritual beliefs and practices of these subjects were a determining factor in reducing the negative impacts caused by the pandemic